2016
DOI: 10.1080/1828051x.2016.1150795
|View full text |Cite
|
Sign up to set email alerts
|

Results of testing the prototype of the AWIN welfare assessment protocol for dairy goats in 30 intensive farms in Northern Italy

Abstract: The AWIN project aimed at developing an on-farm welfare assessment protocol for adult dairy goats. A prototype protocol was tested in 30 intensive dairy goat farms to evaluate its feasibility in farms of different size. Time for applying the prototype was recorded and any other constraint was taken into account. Moreover, data collected during the prototype testing provided information on the prevalence of welfare issues in intensive dairy goat farms in Northern Italy. The prototype included 25 animal-based in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 25 publications
2
54
2
Order By: Relevance
“…Body abscesses, mostly due to Caseous Lymphadenitis, are typically chronic conditions that persevere, supporting the consistency of this indicator over time. Caseous Lymphadenitis is recognized as an endemic disease in many countries (Williamson, 2001), and field studies in Portugal and Italy showed the presence of abscesses in 90% of the visited farms (Battini et al, 2016;Can et al, 2016). These findings support the inclusion of this indicator in a welfare assessment protocol, as it allows the identification of a widespread welfare problem (Ferrante et al, 2012).…”
Section: Discriminative Approachmentioning
confidence: 85%
See 3 more Smart Citations
“…Body abscesses, mostly due to Caseous Lymphadenitis, are typically chronic conditions that persevere, supporting the consistency of this indicator over time. Caseous Lymphadenitis is recognized as an endemic disease in many countries (Williamson, 2001), and field studies in Portugal and Italy showed the presence of abscesses in 90% of the visited farms (Battini et al, 2016;Can et al, 2016). These findings support the inclusion of this indicator in a welfare assessment protocol, as it allows the identification of a widespread welfare problem (Ferrante et al, 2012).…”
Section: Discriminative Approachmentioning
confidence: 85%
“…All assessments followed the welfare assessment prototype protocol developed by the AWIN project for lactating dairy goats in intensive husbandry systems, which comprises 25 animal-based indicators structured in accordance with the 4 principles and 12 criteria developed by Welfare Quality [Botreau et al (2007a); for details on the description of animal-based indicators see Battini et al (2015Battini et al ( , 2016 and Can et al (2016)]. The AWIN prototype protocol combines 14 indicators at group level and 11 indicators at individual level, which are assessed to produce each indicator's prevalence.…”
Section: Farm Sample and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The AWIN prototype protocol was applied on all the 60 farms by the same single observer per country [17]. Observers received a common training on the whole prototype protocol, including the description and application of each indicator and the order of data collection (Table 1) [17]. Preliminary studies revealed a good inter-observer reliability (on PC1, r = 0.910 and PC2, r = 0.906; p = 0.001) [18] of adequately trained observers.…”
Section: Methodsmentioning
confidence: 99%